Hadith Daif dan Palsu dalam Pengurusan Jenazah: Kajian Terhadap Sumber dan Rujukan Masyarakat Islam di Mukim Kutan, Tumpat, Kelantan: Weak and Fabricated Hadith in Funeral Rituals: A Study of Muslim Community Sources and References in Kutan Area, Tumpat, Kelantan - Muhammad Faleh Lai, Nur Farha; Ahmad Shah, Faisal (Jurnal Usuluddin, 2020)
There are a few practices in Muslims funeral rituals today are stemming from tradition that influenced by the customs and culture of community. There are also rituals that have been practiced through this generation based on weak and fabricated hadiths. Therefore, this quantitative study which involves 361 respondents is to identify the source of funeral rituals for Muslim community in Mukim Kutan, Tumpat Kelantan. Several weak and fabricated hadiths in funeral rituals theme have been selected to see the relevance with community practice. As a result, the sources used by the Muslim community in funeral rituals are from Quran and sunnah, Shāfi‘iyyah’s view, weak, too weak and fabricated hadiths, also based on customary heritage. However, it is undeniable the practices that consistent to the teaching of Quran and sunnah still dominate in funeral rituals but there are also practices that contradict to sunnah and Shāfi‘iyyah’s view.